THE ROLE OF FISH PROCESSING INDUSTRY IN SUPPORTING RURAL LOCAL ECONOMIC SUSTAINABILITY: A CASE STUDY OF MAJA VILLAGE, KALIANDA DISTRICT - Hutama, Surya; Desta Lia,; Rahman, Yudha; Saputri, Dessy Reza (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Fulfilling the lives of Indonesian people in coastal villages requires a direct active role from the community, government, community institutions and the private sector. One of the fishery processing industries which has great potential is in Maja Village with processed fishery products produced in the form of processed salted fish. Rural communities can play a direct role in solving problems according to regional conditions, and the government can provide assistance and management in realizing local economic sustainability. Sustainable development is access to the basic necessities of life to ensure that people can be economically, socially and politically active in their communities, so attention needs to be given to development and the provision of socio-economic facilities to stem the rate of rural-urban migration. Data collected from interviews, observations and documentation were then processed by identifying value chain activities in the salted fish processing industry in Maja Village and village economic sustainability competencies from each value chain in the salted fish processing industry. The identification results show that in marketing there is still collector intervention which reduces processor profits. For this reason, the sales chain through collectors needs to be stopped. In realizing local economic sustainability, several components that need to be improved are the quality of human resources in the fish processing community and the placement of the right people in each salted fish processing chain. Collaboration with partners who provide regular coaching to improve the quality and diversification of salted fish products. The final component is involving the entire fish processing community in every main and supporting actor in salted fish processing, so that they can work together with the same vision.